2017
DOI: 10.3390/su9122207
|View full text |Cite
|
Sign up to set email alerts
|

Climate Changes and Their Impact on Agricultural Market Systems: Examples from Nepal

Abstract: Abstract:Global climate models foresee changes in temperature and precipitation regimes that shift regional climate zones and influence the viability of agricultural market systems. Understanding the influence of climate change on the different sub-sectors and functions of a market system is crucial to increasing the systems' climate resilience and to ensuring the long-term viability of the sectors. Our research applies a new approach to climate change analysis to better understand the influence of climate cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…Increased temperature and rainfall were reported to have both positive and negative impact on crop product markets in different regions of Nepal. This ranged from increased production costs, increased prices, changes in product quality, changes in consumption patterns and shifting of plantation season [44].…”
Section: Climate Change and Food Marketsmentioning
confidence: 99%
“…Increased temperature and rainfall were reported to have both positive and negative impact on crop product markets in different regions of Nepal. This ranged from increased production costs, increased prices, changes in product quality, changes in consumption patterns and shifting of plantation season [44].…”
Section: Climate Change and Food Marketsmentioning
confidence: 99%
“…Cultivation of certain nuts and other cash crops, provides a potential way to adapt agricultural practices to meet these and other challenges [60]. As Barrueto et al [5] have shown, the climate of Nepal is suitable for both macadamia and walnut value-chains at present and under projected climate change scenarios even though growing zones will undergo a regional and elevational shift, as introduced above.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…The commercialisation of walnuts could lead to the substitution in the markets of locally-produced walnuts for those that are currently imported from neighbouring countries [62]. The commercialisation of macadamia has the potential to supply both local and international markets [60]. Moreover, land can be used more efficiently: macadamia growers reported that they have started to intercrop macadamia with coffee.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…In this respect, the expansion of export-base commodities is of tremendous importance to the overall development of the economy (Awe and Ajayi 2009;Bala 2015). Climate change has an impact on market systems that typically involve the provision and sale of goods and services in formal and informal markets (IPCC 2007a, b; Barrueto et al 2017). The effects and impact of climate change depend strongly on the market system and the regional context (Mendelsohn et al 2000; Barrueto et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Climate change has an impact on market systems that typically involve the provision and sale of goods and services in formal and informal markets (IPCC 2007a, b; Barrueto et al 2017). The effects and impact of climate change depend strongly on the market system and the regional context (Mendelsohn et al 2000; Barrueto et al 2017). Out of all market systems, natural resource-based market systems, especially the agricultural systems, by extension, food security, are highly vulnerable to the different impacts of climate change (Mendelsohn et al 2000; Barrueto et al 2017;Lobell et al 2008).…”
Section: Introductionmentioning
confidence: 99%